Karachi : Our Stories in Our Words - Edited by Maniza Naqvi (Karachi Oxford University Press, 2013)
The book is a collection of stories and voices from all over Karachi, written for a story-writing competition arranged by Oxford University Press Pakistan$1 (Band is based on the idea that everyone has a good story to tell. These stories, written by many individuals separately, together chronicle the city and its life. Karachi as a cosmopolitan city of prosperity and opportunity is a strong theme$1 (Ba city where people from all over the country and continent mingle and live in close proximity. There are stories of kindness and empathy. And there are themes of deep income disparity and social injustice. There is nostalgia for a time gone by in Karachi, a new awareness of its past history, a love of the beach and the sea. There is deep pain in these stories$1 (Bof the loss of loved ones, of violence and murder and target killings$1 (Band a real sense of belief and hope for a better future.s
Keywords: Pakistani Literature (English)